2016
DOI: 10.1126/sciadv.1500827
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous structural transition and crystal formation in minimal supramolecular polymer model

Abstract: A comprehensive minimalistic model for spontaneous structural transition that is governed by distinct molecular interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 61 publications
4
71
0
2
Order By: Relevance
“…[45][46][47][48] Importantly, we found that in addition to functioning as a crosslinker of the network, adding a crosslinker also modulates the size and surface chemistry of the spherical aggregates that act as depots of unreacted building block 4, dictating the self-assembly pathway of the low molecular weight gelator material over the various stages of nucleation, fiber growth, and bundling (Scheme 2). However, this method of modulating the materials properties can prove more complex as not all crosslinkers are equivalent in how they can interact with the scaffold monomers during their self-assembly process.…”
Section: Doi: 101002/adma201603769mentioning
confidence: 96%
“…[45][46][47][48] Importantly, we found that in addition to functioning as a crosslinker of the network, adding a crosslinker also modulates the size and surface chemistry of the spherical aggregates that act as depots of unreacted building block 4, dictating the self-assembly pathway of the low molecular weight gelator material over the various stages of nucleation, fiber growth, and bundling (Scheme 2). However, this method of modulating the materials properties can prove more complex as not all crosslinkers are equivalent in how they can interact with the scaffold monomers during their self-assembly process.…”
Section: Doi: 101002/adma201603769mentioning
confidence: 96%
“…In order to investigate the unusual two‐step gelation (as shown in Figure a) in terms of the underlying supramolecular process, a combination of spectroscopic and microscopic techniques was employed. Time‐dependent TEM images (Figure 2b) exhibited a morphological transformation from spheres to fibers over time suggesting a molecular rearrangement of the hypergelator, as observed for another Fmoc‐protected gelator . Powder X‐ray diffraction (PXRD) performed on lyophilized hydrogels that were frozen at similar time‐points (Figure 2c) showed the emergence of specific, nonsharp peaks over time, indicating the formation of long‐range order in the self‐assembled structures.…”
Section: Characteristics Of the Studied Peptide Analogues The Originmentioning
confidence: 99%
“…26 FASAAs are the minimal representation of this class of hydrogelators and studies of these compounds have focused on FASAA analogues of coded amino acids, namely Fmoc-phenylalanine (Fmoc-Phe) and Fmoc-tyrosine (Fmoc-Tyr). 32,33 Fmoc-DOPA is especially interesting due to the multifunctional nature of the catecholic moiety, which is capable to act as an antioxidant, radical trapper, metal chelator, oxidizable reducing agent, etc. 13 Later studies reported the pH-dependent gelation of Fmoc-Tyr, where a gradual decrease in pH from alkaline to acidic led to protonation of the carboxylate group and to the subsequent conversion of solubilized Fmoc-Tyr to ordered fibrillar assemblies in a gel matrix.…”
Section: Introductionmentioning
confidence: 99%